Efek Moderasi Kebijakan Dividen pada Pengaruh Profitabilitas terhadap Nilai Perusahaan Manufaktur - I Made Purba Astakoni; I Wayan Wardita; Ni Putu Nursiani (Universitas Warmadewa, 2019)
Abstract The main goals of companies going public, namely to generate profits to increase the prosperity of shareholders through increasing the value of the company. This research aims is to analyze the profitability has an effect on company value and the dividend policy is capable of moderating variables on the effect of profitability on firm value. This research was conducted at the cosmetics sector and household needs manufacturing companies listed on the IDX for the period 2010-2017, so that the data analyzed is panel data. The data analysis technique uses the Partial Least Square (PLS) approach. PLS is a model of Structural Equation Modeling (SEM) based on components or variants. The results of the analysis show that profitability has no significant positive effect on firm value. The existence of dividend policy as a moderating variable is not able to strengthen the influence of profitability on firm value and vice versa. Abstrak Tujuan utama dari perusahaan adalah go public, yaitu untuk meningkatkan nilai pemegang saham melalui peningkatan nilai perusahaan. Penelitian ini bertujuan untuk menganalisis profitabilitas dari nilai perusahaan dan kebijakan dividen pada nilai perusahaan. Tercantum di BEI untuk periode 2010-2017, sehingga data yang dianalisis adalah panel data. Analisis data menggunakan pendekatan Partial Least Square (PLS). PLS adalah model Structural Equation Modeling (SEM) berdasarkan komponen atau varian. Hasil analisis menunjukkan bahwa profitabilitas tidak berpengaruh positif signifikan terhadap nilai perusahaan. Keberadaan kebijakan dividen sebagai variabel moderasi tidak mampu memperkuat pengaruh profitabilitas terhadap nilai perusahaan dan sebaliknya.